Reversible Photochemical Control of Doping Levels in Supported Graphene - Wang, Hai I.; Braatz, Marie-Luise; Richter, Nils; Tielrooij, Klaas-Jan; Mics, Zoltan; Lu, Hao; Weber, Nils-Eike; Muellen, Klaus; Turchinovich, Dmitry; Klaeui, Mathias; Bonn, Mischa (Journal of Physical Chemistry C, 2017)
Controlling the type and density of charge carriers in graphene is vital for a wide range of applications of this material in electronics and optoelectronics. To date, chemical doping and electrostatic gating have served as the two most established means to manipulate the carrier density in graphene. Although highly effective, these two approaches require sophisticated graphene growth or complex device fabrication processes to achieve both the desired nature and the doping densities with generally limited dynamic tunability and spatial control. Here, we report a convenient and tunable optical approach to tune the steady-state carrier density and Fermi energy in graphene by photochemically controlling the concentration of adsorbed molecular O2, a p-dopant in graphene, using femtosecond pulsed laser irradiation in the UV range. As an all-optical approach, it allows spatial control over doping levels. Combined terahertz (THz) spectroscopy and electrical device measurements reveal that the Fermi level in laser-illuminated graphene can be controllably and reversibly tuned between p- and n-type in a large range (over ∼600 meV from -420 to +180 meV) by readily tuning the peak intensity and the duration of the laser irradiation treatment. Furthermore, we demonstrate that our photochemical approach for doping of graphene allows one to optically write doping structure with spatial control. Given the ease, effectiveness, and simplicity of the method, this photochemical doping mechanism offers a simple, reversible approach to control the steady-state electronic and optical properties of graphene.
CRIS-Team Scopus Importer:2023-03-27